ANALISA UNJUK KERJA TWO STROKE MARINE DIESEL ENGINE BERBAHAN BAKAR CAMPURAN MINYAK SOLAR DAN BIODIESEL MINYAK KELAPA PADA BEBAN SIMULATOR FULL LOAD - M Haris Sochibul Kirom; Muhammad Shah; Edi Haryono (Proceedings Conference on Marine Engineering and its Application, 2020)
As the era develops, the need for petroleum is getting bigger as a fuel so thatinnovation is needed to create renewable energy that can be continuously renewed and utilized,one of which is by creating biodiesel. Biodiesel is a fuel produced from animal fats and vegetableoils through a transesterification process. One of the crops that has the potential to becomebiodiesel is coconut, because Indonesia has the largest coconut plantation in the world. Inaddition, coconut oil also has a very high ester content when compared to other vegetable oils.This study aims to analyze the performance of marine diesel engines under full load conditionsusing mixed fuels, namely diesel and coconut oil biodiesel for power, torque, and gsfc. In thisstudy, the most optimal variation of the fuel mixture on the performance of marine dieselengines. From the test results, it can be concluded that the mixture of coconut oil biodiesel withdiesel fuel increases the power produced with a torque of 239.6343 Nm. The use of the fuelmixture increases the performance of the diesel engine so that the power and torque produced ishigher than using Pertamina Dex alone. From the results of research, the B30 fuel has the highestpower and torque and the B30 fuel also has the lowest gsfc value.